HUBUNGAN ANTARA INDEKS MASSA TUBUH DENGAN KEJADIAN HERNIA INGUINALIS DI RSUD DR. M. HAULUSSY AMBON - Rezky N. P. Salampessy; Achmad Tuahuns; Johan B. Bension (Fakultas Kedokteran Universitas Pattimura, 2019)
Introduction: One of the risk factors that can affect or increase the occurrence of inguinal hernia is overweight and obesity. Several studies have different opinions, that the incidence of inguinal hernia is lower in overweight and obesity compared with normal weight. Method: This study aims to determine the relationship of body mass index to the incidence of inguinal hernia in hospitals dr. M. Haulussy Ambon. The research design used is descriptive analytic with cross-sectional approach using secondary data in the form of medical record in RSUD dr. M. Haulussy. The method used for sampling using purposive sampling technique is all medical records of inguinal hernia patients who meet inclusion criteria and tested statistically with Chi-Square. Result: The samples obtained were 60 patients, consisting of 30 patients (50%) diagnosedinguinal hernia and 30 patients (30%) were diagnosed not inguinal hernias. Chi-Square statistical test results obtained probability value = 0.988 (p> α = 0.05) with value = 0.325. Conclusion: The results of this statistical analysis show that there is no significant relationship between body mass index and the incidence of Inguinal Hernia In RSUD dr. M. Haulussy Ambon.